Adversity Quotient dan Kepercayaan Diri Karyawan yang Mengalami Workplace Bullying - Putri, Azzahra Shakila Meisa; Bantam, Dian Juliarti (Universitas Negeri Makassar, 2025)
Workplace bullying is a criminal act committed by employees against other employees and can lead to a decline in self-confidence. Therefore, adversity intelligence is needed as a form of intelligence that will help individuals face and overcome difficulties such as workplace bullying. The purpose of this study is to determine the relationship between adversity quotient and self-confidence among employees who experience workplace bullying in Yogyakarta. The research method used a quantitative research approach with a correlational design, employing purposive sampling techniques, with the research subjects being employees who have experienced workplace bullying in Yogyakarta. Based on the correlation analysis results, there is a strong and significant positive correlation between adversity quotient and self-confidence among the research respondents. Therefore, it can be concluded that the higher an individual's adversity quotient, the higher their self-confidence.